Measuring Tourist Satisfaction Index On Attraction, Amenities, Accessibility, And Ancillary Service (Case Study Of Angke Kapuk Mangrove Nature Park, Jakarta) - Imam Ardiansyah; Hari Iskandar; Antonius Rizki Krisnadi; Yudhiet Fajar Dewantara (International Journal of Entrepreneurship and Sustainability Studies, 2023)
Angke Kapuk Mangrove Nature Park is a nature-based tourist attraction – nautical, part of the Angke Kapuk Area. It analyzes consumer behaviour through understanding consumer characteristics, the travel decision process, and the suitability between the attributes offered and those needed by visitors to provide a high satisfaction level. This study was conducted to find out more about the level of tourist satisfaction with the components of tourism. It analyzes consumer behaviour through understanding consumer characteristics, the travel decision process, and the suitability between the attributes offered and those needed by visitors to provide a high satisfaction level. This data was collected using quantitative research. The research method used in this study is the Customer Satisfaction Index and Important Performances Analysis. Based on the results of the analysis using the Customer Satisfaction Index (CSI) method showed that the respondents were satisfied with the performance of the services provided by the Mangrove Natural Tourism Park, Angke Kapuk. Tourists are satisfied with the Attraction component with a value of 71.7% Then tourists were satisfied with the Amenity component with a value of 70.8%. In addition, tourists are also satisfied with the Accessibility component with a value of 69.0%. Finally, tourists are quite satisfied with the Ancillary Service component with a value of 63.9%. The IPA is a strategic tool for tourism managers or researchers to assess the quality of tourism services by providing guidelines to prioritize areas of focus for improvement.